“About a Symbol”: Genesis and Parallels. Article Two. Dostoevsky as a Symbolist - Anna I. Reznichenko (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2021)
The article is devoted to the literary and philosophical origins of Sergei Durylin’s report “On a Symbol in Dostoevsky” (the report was read in 1926 at a meeting of the Commission for the Study of Dostoevsky at the Literary Section of GAKhN). The history of the report in the context of the Literary Section is considered. Аbstracts and debates on the report are published for the first time. The relationship of Durylin’s ideas with the complex of Dostoevsky’s interpretations, developed by both the Symbolists (G.I. Chulkov) and Russian religious philosophers (P.A. Florensky, A.F. Losev) is shown. Both the report “On a Symbol in Dostoevsky’s” and the subsequent report “Landscape in Dostoevsky’s” are devoted to an anthropological and Christological story, connected with the symbolism of the setting sun, the symbolism of “oblique rays”, and its embodiment in Dostoevsky’s novels. Both texts are a continuation and a development of the same theme. A landscape is an artist’s mapping of nature, the created world; interiors are the artist’s image of the anthropomorphic world, the human space. The ontological symbol receives its sociocultural projection: a landscape or an interior. The problem of the relationship between the mapping/image and the object of the image, the problem of the ontological status of reality and its embodiment in the artistic/mythopoetic language, reflected in the report, corresponded to the focus of GAKhN on the development of a new “language of things” and a new concept of the humanitarian knowledge. The article is timed to coincide with the 200th anniversary of F.M. Dostoevsky, the 135th anniversary of S.N. Durylin, and the 100th anniversary of GAKhN.